1994
DOI: 10.1007/bf02578245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary n−3 and n−6 polyunsaturated fatty acids on lipid‐metabolizing enzymes in obese rat liver

Abstract: This study was designed to examine whether n-3 and n-6 polyunsaturated fatty acids at a very low dietary level (about 0.2%) would alter liver activities in respect to fatty acid oxidation. Obese Zucker rats were used because of their low level of fatty acid oxidation, which would make increases easier to detect. Zucker rats were fed diets containing different oil mixtures (5%, w/w) with the same ratio of n-6/n-3 fatty acids supplied either as fish oil or arachidonic acid concentrate. Decreased hepatic triacylg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The ensuing increase of membrane fluidity is reported to generate a number of responses, such as the enhancement of membrane-associated phospholipase A 2 activity [43], proton leakage [44,45], and Ca 2ϩ efflux [46]. Furthermore, changes in phospholipid fatty acid composition can alter the activity of carnitine palmitoyltransferase I [47,48] and of the pyruvate carrier [49,50]. If correct, the interaction of PC-TP with mitochondria may have a profound effect on mitochondrial function, including an increased ␤-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The ensuing increase of membrane fluidity is reported to generate a number of responses, such as the enhancement of membrane-associated phospholipase A 2 activity [43], proton leakage [44,45], and Ca 2ϩ efflux [46]. Furthermore, changes in phospholipid fatty acid composition can alter the activity of carnitine palmitoyltransferase I [47,48] and of the pyruvate carrier [49,50]. If correct, the interaction of PC-TP with mitochondria may have a profound effect on mitochondrial function, including an increased ␤-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing membrane polyunsaturation of cells has been shown to modify the activity of various membrane enzymes (94,95). A review of major membrane proteins concluded that 5Ј nucleotidase activity increased with greater membrane unsaturation, adenylate cyclase varied between tissues, and Na ‫ם‬ -K ‫ם‬ ATPase activity decreased with increasing polyunsaturation (96).…”
Section: Influence Of Membrane Lipids On Membrane Proteinsmentioning
confidence: 98%
“…C17:0 as the internal standard, after methylation according to the procedure of Christie (31) and separation by gas chromatography, as previously described (32). ECs and congeners were purified from lipid extracts and determined by isotope dilution liquid chromatography-atmospheric pressure chemical ionization-mass spectrometry using deuterated standards as described in the study by Bartelt et al (33).…”
Section: Lipid and Ec Analysesmentioning
confidence: 99%